Oryzalin-induced polyploidy in Vanda limbata (Blume): Phenotypic assessment - Murni Dwiati; Wahyu Nur Hasam; Agus Hery Susanto (Indonesian Society for Biochemistry and Molecular Biology, 2025)
Background: Vanda limbata is a natural orchid species found on Java Island, commonly known as V. limbata 'Jawa.' Enhancing plant vigor is essential to increase its potential as an ornamental plant, with one promising approach being induced polyploidy using chemical mutagens such as oryzalin. Objective: This study aimed to evaluate the effect of oryzalin on inducing polyploidy in V. limbata cultured in vitro. Method: Oryzalin was applied at concentrations of 0, 25, 50, 75, and 100 µM, with five replications for each treatment, resulting in 25 experimental units. Several morpho-physiological and anatomical traits were measured as indicators of polyploidy. Results: The results demonstrated that oryzalin at 100 µM was the most effective concentration for inducing polyploidy in V. limbata cultured in vitro. This was particularly evident in traits such as reduced leaf length, increased leaf width, enhanced adventitious shoot formation, and enlarged stomatal width. Conclusion: Oryzalin, when applied at appropriate concentrations, can be effectively used to induce polyploidy in V. limbate.